Improved management can be achieved by introducing additional parameters in the syndromic diagnosis of nonviral sexually transmitted infections at low-resource settingsAJOG Global Reports at a Glance - Subash C. Sonkar, PhD; Geetika Arora, MSc; Kirti Wasnik, MPharm; Mashook Ali, PhD; Pratima Mittal, MD; Daman Saluja, PhD (Elsevier, 2022)
BACKGROUND: The syndromic approach is a simple and affordable strategy for the management of sexually transmitted infections in countries with low-resource settings. However, because of the lack of specificity and accuracy, the risk of overuse and misuse of antibiotics is very high. Here, we proposed a more specific and accurate algorithm compared with the current algorithm used for syndromic case management of 3 common sexually transmitted pathogens and compared its precision with laboratory-based tests. OBJECTIVE: This study aimed to report a comparative account of the accuracy of existing syndromic case management guidelines followed in mainstream hospitals, for taking care of patients with nonviral sexually transmitted infections, concerning an approach involving an alternative algorithm formulated in our laboratory followed by polymerase chain reaction testing. STUDY DESIGN: This was an observational study that compared the data between 2 categories based on diagnostics accuracy and treatment. In category I, symptoms of infection were scored on the basis of the existing National AIDS Control Organization and National AIDS Control Programme guidelines, and patients were treated before testing by polymerase chain reaction. In category II, patients were recruited on the basis of the National AIDS Control Organization and National AIDS Control Programme guidelines with additional alternative syndromic case management parameters. All samples were tested by polymerase chain reaction for Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis and clinically correlated before giving the treatment. RESULTS: In category I, among 646 women with symptomatic infection, only 46 (7.82%) tested positive by polymerase chain reaction assay for at least 1 of the pathogens, and 600 (92.87%) tested negative for infection by any of the 3 pathogens. The total estimated percentages of the overuse and misuse of antibiotics were 92.87% and 8.69%, respectively. Correct and complete treatment based on laboratory outcome compared with National AIDS Control Programme guidelines was 42 of 46 (91.30%). The estimated overuse of azithromycin and cefixime (Gray Kit) was 29.69%, the estimated overuse of a combination of doxycycline, cefixime, and metronidazole (Yellow Kit) was 29.87%, and the estimated overuse of a combination of doxycycline, cefixime, metronidazole, and azithromycin (Gray with Yellow Kit) was 11.45%. In category II, wherein patients were treated using an alternative syndromic approach and polymerase chain reaction diagnostics, 243 of 319 patients (76.15%) were infected with either of the pathogens (Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis), whereas 76 of 319 patients (23.82%) were negative for any of the 3 pathogens. Among 243 patients with infection, 99 of 243 (40.74%) were infected with a single pathogen, whereas 144 of 243 (59.20%) were coinfected. Of 144 coinfected patients, the percentage of Chlamydia trachomatis + Neisseria gonorrhoeae infection was the highest (51.38%), followed by coinfection with all 3 pathogens (30%). Coinfection with Chlamydia trachomatis + Trichomonas vaginalis was 9.72%, and coinfection with Neisseria gonorrhoeae + Trichomonas vaginalis was 9.03%. The estimated overuse of antibiotics was found to be 23.82% only. CONCLUSION: The proposed alternative strategies of syndromic case management can reduce the percentage of misuse and overuse of antibiotics from 92.87% to 23.82%. Moreover, syndromic case management alone was insufficient for disease management.